Enhanced anaerobic digestion of primary sludge with additives: Performance and mechanisms. (November 2020) - Xie, Sihuang; Li, Xuan; Wang, Chengduan; Kulandaivelu, Jagadeeshkumar; Jiang, Guangming
Graphical abstract: Highlights: Different additives were comprehensively evaluated for their impacts on AD. Additives improved methane production & process kinetics at optimal dosage. Activated carbon exhibited apparent synergistic effects with the highest P and k h . The AD microbial community structure was affected by additives. DIET played a significant role for nano magnetite or graphite powder treatment. Abstract: Anaerobic digestion of primary sludge with different additives, namely nano magnetite, graphite powder, activated carbon powder and NiCl2 /CoCl2, were evaluated by biomethane potential tests, kinetics modelling and microbial community analysis. Specific methane yields increased from 136 mL/g VS for primary sludge to 146 mL/g VS, 151 mL/g VS, and 152 mL/g VS for the addition of nano magnetite, graphite powder, and activated carbon powder at optimal dosages, respectively. The first order hydrolysis constant k h increased from 0.488 d -1 to 0.526 d -1, 0.622 d -1, and 0.724 d -1, respectively. Microbial community analysis revealed that the abundance of key bacterial and archaeal populations was positively correlated with hydrolysis and methane production. The enhanced methane production with activated carbon powder was due to shifting methane formation pathway from acetoclastic to hydrogenotrophic methanogenesis. In contrast, nano magnetite and graphite powder additives enhanced the direct interspecies electron transfer evidenced by increased abundance of Methanosaeta and Methanolinea.